(untitled) (The Conference Hub, 2025)
Phraseological units containing ethnonymic components reflect cultural stereotypes, historical experience, and national worldview. This article presents a comparative analysis of ethnonym-based phraseological units in Uzbek and English. The study examines their semantic features, structural patterns, and cultural connotations. By analyzing selected examples, similarities and differences between the two languages are identified. The findings show that while both languages employ ethnonyms to express evaluation and imagery, the cultural motivations and pragmatic functions often differ. The research contributes to contrastive phraseology and intercultural linguistics.